Elevate your scrap sewing projects : 20+ beautiful techniques using your fabric stash - Harrison, Sallieann (Landauer Publishing, 2023)
"Use your sewing scrap fabrics to make impressive, out-of-the-box sewing projects that will wow! Elevate Your Scrap Sewing Projects is filled with 10 super cute projects, from wallets and cushions to pouches, baskets, quilts, soft toys, and more, that include step-by-step instructions, coordinating photography, and expert tips to ensure success. You'll also learn and practice 20 sewing techniques for basket weaving, angled pleats, patchwork piecing, hand embroidery, tiny applique, and other skills. Using both hand and machine techniques to make unique accessories, this is a must-have guide for crafters of every skill level to make something amazing!"--